Peningkatan Keterampilan Membaca dan Menulis melalui Penggunaan Media Kartu Huruf pada Siswa Kelas II di SDI Betun Kota - Kristian Bere; Yanuarius Bria Seran; Marsela Luruk Bere; Damian Puling (Inovasi Pendidikan dan Anak Usia Dini, 2025)
Improving Reading and Writing Skills through the Use of Letter Card Media in Grade II Students at SDI Betun Kota. This research was conducted based on the problem: how to improve the reading and writing skills of grade II students at SDI Betun Kota by using letter card media. This research was conducted using the CAR method. With research actions carried out in two cycles. Each cycle consists of planning, observation of learning activities, and reflection. The target of this research is grade II students at SDI Betun Kota. Data collection techniques were obtained from the results of pre-tests and post-tests as well as observation sheets for teaching and learning activities. From the results of the analysis, it was found that student learning outcomes increased by 58.62%, while the average n-gain value was 0.71. The results of the study indicate that letter card media is one of the media that can be applied in Indonesian language learning. By using letter card media, the reading and writing skills of grade II students at SDI Betun Kota can be improved. This can be seen from the achievement of students' KKM scores and the percentage that increased from cycle I by 53% and in cycle II by 100%. Thus, student learning outcomes increased by 47% when using letter cards.